Assessment of Thailand’s Food Safety Core Capacity in Compliance with International Health Regulations (2005) - Tangkanakul, Waraluk; Vithayarungruangsri, Jongkolnee; Karnasuta, Kanyarat; Kaewklom, Weeraya; Srisantor, Kannikar (Journal of Health Science of Thailand, 2018)
Thailand must develop the capacity to prevent, detect and respond to health threats from food comply with 22 indicators of the International Health Regulations (IHR) 2005. This study aimed to determine the level of food safety capacity and recommendations to improve the capacity of the country. We developed the criterion for assessing food safety capacity in line with IHR’s indicators. Qualitative study was conducted in 12 agencies at central level to assess food safety’s capacity. Self-assessment was conducted by 200 authorities involved in food safety from all provincial health offices. Re-assessment was performed in 14 voluntary provinces by a working group on food safety and quality system development during October 2013 to September 2014. It was found that all agencies at the central level passed all indicators compared to 84.2 percent (64 provinces) at provincial level. The high capacities levels were surveillance, risk communication’s policy whereas response and human resource development had low capacities levels. The average percentage scores obtained from the self-assessment and the working group of 2 provinces (14%) were statistically significant (p<0.05). From study results, Thailand should develop food safety emergency response plan and food and water borne diseases control team specialist at every level.